2004
DOI: 10.1073/pnas.0400984101
|View full text |Cite
|
Sign up to set email alerts
|

Multiarm spirals in a two-dimensional cardiac substrate

Abstract: A variety of chemical and biological nonlinear excitable media, including heart tissue, can support stable, self-organized waves of activity in a form of rotating single-arm spirals. In particular, heart tissue can support stationary and meandering spirals of electrical excitation, which have been shown to underlie different forms of cardiac arrhythmias. In contrast to single-arm spirals, stable multiarm spirals (multiple spiral waves that rotate in the same direction around a common organizing center) have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
69
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 35 publications
4
69
0
Order By: Relevance
“…Bursac et al demonstrated that these surfaces resulted in a similar degree of cardiomyocyte orientation and elongation as the surfaces prepared using microcontact printing of laminin lanes [22] and that they could be utilized as model for electrophysiological studies [22,38].…”
Section: Selection Of Topographical Cues Electrical Field Stimulatiomentioning
confidence: 99%
See 1 more Smart Citation
“…Bursac et al demonstrated that these surfaces resulted in a similar degree of cardiomyocyte orientation and elongation as the surfaces prepared using microcontact printing of laminin lanes [22] and that they could be utilized as model for electrophysiological studies [22,38].…”
Section: Selection Of Topographical Cues Electrical Field Stimulatiomentioning
confidence: 99%
“…To introduce topographical cues (Figure 1), we used a previously established method of abrading polyvinyl cover slips using lapping paper [22,38]. Bursac et al demonstrated that these surfaces resulted in a similar degree of cardiomyocyte orientation and elongation as the surfaces prepared using microcontact printing of laminin lanes [22] and that they could be utilized as model for electrophysiological studies [22,38].…”
Section: Selection Of Topographical Cues Electrical Field Stimulatiomentioning
confidence: 99%
“…Nevertheless, the NRVM has proven to be an effective model for the study of cardiac conduction 45 and reentry. 26,46,47 …”
Section: Limitationsmentioning
confidence: 99%
“…This system has reduced structural complexity compared with the heart per se, which is an advantage when the goal is an understanding of the fundamental properties of wave propagation in cardiac tissue. It has provided a basis for many successful studies of wave propagation at the cellular level (19,30,35), generation of steadily rotating single and multiplearmed spiral waves (8,15), creation of controlled inhomogeneities and simulated defibrillation shocks (18), and propagation disturbances caused by local ischemia-reperfusion injury (6,33).…”
mentioning
confidence: 99%